Método de programação diária de produção nas operações de lavra em minas a céu aberto - Medrado Neto, João da Rocha; Figueiredo, Elon Silva; Faria Neto, José Silvino de (PARAMÉTRICA, 2010)
The present work aims at proposing and developing a method to optimize the decision process of ore extraction and, by means of organized procedures, assure the quality of the ore blending in the working benches of open pit mines. The developed method is not only composed of the main stages of the mining process but also of operational research techniques and mathematical tools. The procedures evaluate the geological composition of the terrain, the available ore masses and the concentrations of minerals. The mathematical model presented also aimed at maximizing the use of existing natural resources, as well as minimizing the cost of the mining, thus making this relation more efficient. The results obtained with the first version of the method resulted in more productive mining operations. Besides, they indicated a significant increase of the life span of the mine.